The Effect of 4 Pillars of Health Education on Blood Sugar Levels in Type 2 Diabetes Mellitus - Collein, Irsanty (Poltekkes Kemenkes Palu, 2023)
Diabetes mellitus occurs more frequently in rural areas than urban areas and occurs more frequently in groups with low education. Type 2 Diabetes Mellitus disease management through the implementation of the four pillars of diabetes treatment, including education, dietary nutrients, exercise, and pharmacology. The study aimed to determine the effect of the 4 pillars of DM health education on blood sugar levels. Pre-experimental research design with a one-group pre-test and post-test design approach using paired t-test. The number of samples is determined by the sample formula to test the hypothesis on the average of two populations with a 33 sample. The samples involved in this study were selected by simple random sampling who met the criteria, namely DM > 3 months, could read and write and were willing to participate in the study. The results of this research is the 4 pillars of health education gave a change in the blood sugar levels of patients before and after health education with a P value of 0.0005 and did not affect the length of suffering from DM. The conclusion is there is an effect of health education on the 4 pillars of DM on the value of blood sugar levels. It is hoped that health workers will maximize health education on the 4 pillars of DM.